Deciphering the microbial composition of biodynamic preparations and their effects on the apple rhizosphere microbiome - Olimi, Expedito; Bickel, Samuel; Wicaksono, Wisnu Adi; Kusstatscher, Peter; Matzer, Robert; Cernava, Tomislav; Berg, Gabriele (Frontiers in Soil Science, 2022)
Soil microbial communities are crucial for plant growth and are already depleted by anthropogenic activities. The application of microbial transplants provides a strategy to restore beneficial soil traits, but less is known about the microbiota of traditional inoculants used in biodynamic agriculture. In this study, we used amplicon sequencing and quantitative PCR to decipher microbial communities of composts, biodynamic manures, and plant preparations from Austria and France. In addition, we investigated the effect of extracts derived from biodynamic manure and compost on the rhizosphere microbiome of apple trees. Microbiota abundance, composition, and diversity of biodynamic manures, plant preparations, and composts were distinct. Microbial abundances ranged between 1010-1011 (bacterial 16S rRNA genes) and 109-1011 (fungal ITS genes). The bacterial diversity was significantly higher in biodynamic manures compared to compost without discernible differences in abundance. Fungal diversity was not significantly different while abundance was increased in biodynamic manures. The microbial communities of biodynamic manures and plant preparations were specific for each production site, but all contain potentially plant-beneficial bacterial genera. When applied in apple orchards, biodynamic preparations (extracts) had the non-significant effect of reducing both bacterial and fungal abundance in apple rhizosphere (4 months post-application), while increasing fungal Shannon diversity and lowering bacterial Shannon diversity. One to four months after inoculation, individual soil microbes showed changes in their abundance such as the reduction of the pathogenic fungus Alternaria, and the enrichment of potentially beneficial bacterial genera such as Pseudomonas. Our study paves way for the science-based adaptation of empirically developed biodynamic formulations under different farming practices to restore the vitality of agricultural soils.